Development and validation of guidance module for children in prison: A study at Kajang women’s prison, Malaysia - Dakir, Jawiah; Mohd Hanapi, Rosilawati; Md Sham, Fariza; Tibek, Siti Rugayah; Badzis, Mastura; Mohd. Awal, Noor Aziah; Ismail@Ibrahim, Siti Maheran; Muhammad Hilmi, Jalil (Sakarya University, 2017)
In Kajang Women’s Prison in Malaysia, there are some inmates who have children, those who were either born while their mothers were in detention or were still small and lactating when their mothers were detained. These children are allowed to stay with their mothers in the prison until they reach the age of 3 years. After the age of 3, they will be sent to their families to be raised if their mothers are still serving the remaining sentence. Preliminary studies regarding children’s upbringing while in prison found that the prison authorities would merely use the general module for children supplied by the Social Welfare Department. There is no specific module designed for children’s education in prison. Due to this void, a draft module (10 sub-modules and 42 sessions) has been developed based on ‘A Study on Requirement & Development of Guidance Module for the Children of Inmates at Kajang Women’s Prison’ and the module was tested on study ‘Validation and Implementation of Guidance Module for Children of Inmates’. The objectives of these two studies are to develop a specific module for the guidance of children in prison, and to test the validity and suitability of the module for implementation by taking into account the appropriate circumstances and situations in the prison. It is developed based on interviews with child guidance experts, prison officers, and round-table discussions attended by health experts and those related to children’s guidance in general. It also involves the use of questionnaires. This module was examined to gauge its validity and suitability, and tested on twenty-one (21) inmates who had children, either living with them in prison or outside. The module is found to be suitable and is acknowledged as appropriate for use by the respondents since the mean score of their understanding was increased exceeding 4 at the end of the study. This module is able to fulfill the need to provide specific guidance to inmates who have children, living inside or outside of prison. © The Turkish Online Journal of Educational Technology